Απόφαση συνεδρίασης του Δημοτικού Συμβουλίου Κοζάνης για την έγκριση δαπάνης μικροφωνικής έγκαταστασης
Απόφαση συνεδρίασης του Δημοτικού Συμβουλίου Κοζάνης για την έγκριση δαπάνης μικροφωνικής έγκαταστασης